Choroidal thickness and vascular microstructure parameters in Chinese school-age children with high hyperopia using optical coherence tomography - Zhu, Dehai; Wang, Hui; Li, Ruoshi; Wen, Jing; Li, Ruiying; Zhao, Jingjing (Frontiers in Pediatrics, 2023)
Background The current study was to evaluate the choroidal thickness (CT) and vascular microstructure parameters in Chinese children with high hyperopia. Methods A total of 23 children with high hyperopia and 29 normal children were enrolled in the study. The measurement of the macular CT, 7 points: the sub-foveal area point, the temporal and nasal points at a radius of 0.5-mm, 1.5-mm, and 3-mm were measured. After binarization of the OCT images, the total choroidal area (TCA), stromal area (SA) as well as the luminal area (LA) were identified and measured. The choroidal vascularity index (CVI) was defined as the ratio of LA to TCA. Results The subfoveal CT (SFCT) in the high hypermetropic group was significantly thicker than that in normal controls (P = 0.019). At 0.5mm, 1.5 mm, and 3.0mm in diameter, the nasal choroidal sectors of the high hyperopia eyes were significantly thicker than that of the control (P < 0.05). There was significant difference in the choroidal vascular parameters. TCA and LA in the high hyperopia eyes was significantly larger than that of the normal control eyes (P = 0.009, P = 0.011; Table 2). SA values were 1086287.55 ± 212712.11 um2 in the high hyperopia eyes and 999712.71 ± 209838.12 μm2 in the control eyes. The CVI and LA/SA ratio values were differed significantly in the two groups (P = 0.019, P = 0.030, respectively). AL was significantly correlated with SFCT (r = − 0.325, P = 0.047), but not significantly correlated with other parameters. Spherical equivalent (SE) was significantly correlated with AL and SFCT (r = -0.711, r = 0.311; P = 0.001, P = 0.016), whereas no significant association between sphere and other parameters. Conclusion The choroidal structure of the high hyperopia eyes was different from the normal control eyes. The thicker SFCT, higher LA, and TCA were characteristic of high hyperopia eyes. Choroidal blood flow may be decreased in amblyopic eyes. SFCT of high hyperopia children abnormally increased and correlated with shorter AL and higher SE. AL and SE affect choroidal structure and vascular density.